1990
DOI: 10.1212/wnl.40.2.309
|View full text |Cite
|
Sign up to set email alerts
|

Corticofugal projections to the motor nuclei of the brainstem and spinal cord in humans

Abstract: We studied corticofugal projections to the motoneurons with Nauta-Gygax's technique in a patient with cerebral infarction of both hemispheres. Motoneurons in the brainstem motor nuclei and spinal anterior horns seem to receive direct cortical projections, except for the oculomotor and abducens nuclei and Onuf's nucleus in the sacral cord.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
0
1

Year Published

1991
1991
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(78 citation statements)
references
References 0 publications
3
74
0
1
Order By: Relevance
“…Evidence from anterograde degeneration studies of corticobulbar connections in macaques, chimpanzees, and humans suggests that there are interspecific differences in the projections of layer V pyramidal neurons of primary motor cortex. Compared to macaques, chimpanzees [Kuypers, 1958b] and humans [Kuypers, 1958a;Iwatsubo et al, 1990] were observed to have a greater density of degenerating fibers within the trigeminal motor nucleus and all parts of the facial nucleus following cortical ablation. This increase in direct cortical input to orofacial motor nuclei is attended by a reduction in indirect cortical projections to the reticular formation.…”
Section: Phylogenetic Patterns Of Npnfp-immunoreactive Neuron Distribmentioning
confidence: 91%
See 1 more Smart Citation
“…Evidence from anterograde degeneration studies of corticobulbar connections in macaques, chimpanzees, and humans suggests that there are interspecific differences in the projections of layer V pyramidal neurons of primary motor cortex. Compared to macaques, chimpanzees [Kuypers, 1958b] and humans [Kuypers, 1958a;Iwatsubo et al, 1990] were observed to have a greater density of degenerating fibers within the trigeminal motor nucleus and all parts of the facial nucleus following cortical ablation. This increase in direct cortical input to orofacial motor nuclei is attended by a reduction in indirect cortical projections to the reticular formation.…”
Section: Phylogenetic Patterns Of Npnfp-immunoreactive Neuron Distribmentioning
confidence: 91%
“…This increase in direct cortical input to orofacial motor nuclei is attended by a reduction in indirect cortical projections to the reticular formation. It should be noted, however, that older methods for silver impregnation of degenerating axons, such as the Nauta-Gygax method employed by Kuypers [1958a, b] and Iwatsubo et al [1990], are known to produce capricious and inconsistent results [Heimer and Robards, 1981], and therefore should be interpreted with caution. However, ethical considerations prohibit the application of more modern tract-tracing methods to study the distribution of cortical axon terminals in the orofacial motor nuclei of great apes and humans.…”
Section: Phylogenetic Patterns Of Npnfp-immunoreactive Neuron Distribmentioning
confidence: 99%
“…In fact, in contrast to the monkey cortical larynx area, electrical stimulation of the human LPA does indeed produce vocalization (Penfield and Boldrey, 1937), and lesions may cause mutism and other speech disorders. Furthermore, the human LPA projects monosynaptically to the laryngeal lower motor neurons in the nucleus ambiguus (Kuypers, 1958;Iwatsubo et al, 1990), while the monkey larynx area projects to the nucleus ambiguus only indirectly via synapses in the reticular formation (Simonyan and Jü rgens, 2003;Jü rgens and Ehrenreich, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, although external bladder sphincter motoneurons in ON directly innervate the striated sphincter muscles and are under voluntary control of the motor cortex, albeit not directly (Iwatsubo et al, 1990), they also behave as autonomic motoneurons. For example, ON motoneurons are smaller than most other somatic motoneurons.…”
Section: Motoneurons Innervating Bladder and Bladder Sphinctermentioning
confidence: 99%